An Optical Surface Applicator for Intraoperative Photodynamic Therapy. Issue 6 (6th October 2019) - Chamberlain, Sarah; Bellnier, David; Yendamuri, Sai; Lindenmann, Joerg; Demmy, Todd; Nwogu, Chukwumere; Ramer, Max; Tworek, Larry; Oakley, Emily; Mallory, Matthew; Carlsen, Lindsey; Sexton, Sandra; et al.
Abstract : Background and Objectives: Intraoperative photodynamic therapy (IO‐PDT) is typically administered by a handheld light source. This can result in uncontrolled distribution of light irradiance that impacts tissue and tumor response to photodynamic therapy. The objective of this work was to characterize a novel optical surface applicator (OSA) designed to administer controlled light irradiance in IO‐PDT. Study Design/Materials and Methods: An OSA was constructed from a flexible silicone mesh applicator with multiple cylindrically diffusing optical fibers (CDF) placed into channels of the silicone. Light irradiance distribution, at 665 nm, was evaluated on the OSA surface and after passage through solid tissue‐mimicking optical phantoms by measurements from a multi‐channel dosimetry system. As a proof of concept, the light administration of the OSA was tested in a pilot study by conducting a feasibility and performance test with 665‐nm laser light to activate 2‐(1′‐hexyloxyethyl) pyropheophorbide‐a (HPPH) in the thoracic cavity of adult swine. Results: At the OSA surface, the irradiance distribution was non‐uniform, ranging from 128 to 346 mW/cm 2 . However, in the tissue‐mimicking phantoms, beam uniformity improved markedly, with irradiance ranges of 39–153, 33–87, and 12–28 mW/cm 2 measured at phantom thicknesses of 3, 5, and 10 mm, respectively. The OSA safely delivered the prescribed light dose to the thoracic cavities of four swine. Conclusions: The OSA can provide predictable light irradiances for administering a well‐defined and potentially effective therapeutic light in IO‐PDT. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.